CHARACTERIZATION OF PROGNOSTIC FACTORS OF BREAST CANCER AMONG WOMEN WITH THIS CONDITION ATTENDED BY THE BRAZILIAN UNIFIED HEALTH SYSTEM IN THE MUNICIPALITY OF BAGÉ, RIO GRANDE DO SUL, BRAZIL - Laila, Hanan Jumah Eid Ahmah; Zenkner, Jenifer Rafaela Grzeczinski; Araújo, Maurício Collares; Becker, José Dionísio de Lima; Pereira, Adriana Dall’Asta (Mastology, 2019)
Objective: This study aimed to characterize the prognostic factors of breast cancer among women with this pathology treated by the Brazilian Unified Health System in the Municipality of Bagé, Rio Grande do Sul, which comprises the municipalities of the 7th Regional Health Coordination. Methods: This study was documentary, retrospective and quantitative in nature and based on the analysis of the medical records of patients undergoing cancer treatment who were attended at the oncological treatment unit in Bagé, from December 2010 to June 2017. Results: The results showed a total of 349 patients with breast cancer in the analyzed period, and their age ranged from 24 to 90 years, with the highest frequency presenting in white women in the left breast (42%). Most of the cancers were smaller than 2 cm (53.9%), with no lymph node involvement (57%) and without distant metastases (93.4%), and the majority of patients were diagnosed in the early stages, I (36.4% %) and II (32.4%). Regarding the anatomopathological and immunohistochemical characteristics, invasive ductal carcinoma was the most common type (79.7%), the histological grade II was present in more than half of cases (56.5%), and 78.8% of the patients presented with the expression of hormone receptors, whereas 16% had HER2 overexpression; the luminal subtype B was present in 64.8% of the patients. Conclusion: Thus, it is noted that most patients are diagnosed in the early stages. Nonetheless, it is still necessary to adopt measures that guarantee diagnosis in pre-invasive phases.